CERAI GUGAT KARENA HIPERSEKS PERSPEKTIF MAQA>S{ID AL-‘USRAH (Studi Putusan Nomor 0060/Pdt.G/2020/PA.Jbg Di Pengadilan Agama Jombang) - muthiah algarnisah; Fathul Chodir (Saintifika Islamica, 2022)
A man and a woman who want to build a physical and spiritual bond between the two of them make a marriage. This aims to form a family that is sakinah, mawaddah and warahmah as this has been stated in the Al-Quran surah Ar-rum: 21. One of the goals of marriage is to fulfill the spiritual needs of both of them. What becomes one of the inner needs is sexual intercourse. Sexual relations must be balanced from both. So that one party does not feel that it is just an object. For example, in the case at the Jombang Religious Court regarding divorce caused by different sex frequencies, in this case a husband has a high sex frequency, this is often called hypersex, because the frequency of sex is so different that the wife is unable to serve her husband. The problem of divorce that occurs because of the frequency of different sexes is a contemporary problem, therefore using Maqasid Al-'Usrah as a solution to solve this problem. Based on the results obtained from this study, the judge decided this case with considerations referring to Article 116 letter (f) of the Islamic Law Compilation and Article 19 letter (f) PP No. 9 of 1975 concerning the implementation of Law No. 1 of 1974 concerning marriage jo. The reason for the judge using the legal basis is that the things that caused the divorce have been fulfilled. However, hypersexuality is not included in the reason for divorce, but because this hypersexuality results in continuous strife for both of them, this hypersexuality is taken as the reason for the divorce. Meanwhile, from the perspective of Maqasid Al-'Usrah itself, because of the different frequency of sex in this case, it causes strife, the purpose of marriage cannot be realized. Based on benefit, it is appropriate to be granted by the Jombang Religious Court judge to decide on the divorce.